Equivalence Transformation for Neutral Differential Equations: Oscillation of Solutions - Ağacık Zafer; Tuncay Candan; Zeynep Nilhan Gürkan (Mathematics)
We introduce an equivalence transformation to study the oscillation behavior of solutions for linear neutral differential equations of canonical and noncanonical types. The new approach leads to several novel oscillation criteria. Moreover, we show that the same arguments can be applied to nonlinear neutral equations under suitable monotonicity conditions. The importance of the results is also supported by examples.